Effects of NaOH and Na2CO3 pretreatment on the saccharification of sweet sorghum bagasse - García-Negrón, Valerie; Stoklosa, Ryan J.; Toht, Matthew J. (Frontiers in Chemical Engineering, 2024)
In this work, the chemical composition, chemical structures, and sugar release were evaluated for sweet sorghum bagasse (SSB) biomass in response to alkaline pretreatments and enzymatic hydrolysis. Five different ratios of 2 M sodium hydroxide (NaOH) and sodium carbonate (Na2CO3) solutions were used for biomass fractionation along with two heat treatment conditions, 85°C and 150°C for 1 h. Sugar yields from enzymatic hydrolysis were measured at different durations up to 72 h. SSB samples pretreated at high temperature using alkaline solutions containing equal amounts of Na2CO3 and NaOH favored retaining cellulose content (up to 90%) while effectively removing hemicellulose (65%) and lignin (92%). The high-temperature pretreatment conditions resulted in improved delignification, higher sugar concentrations, and sugar yields. Pretreatment solutions consisting of 50% or more NaOH produced higher glucose yields (85%–90%) and total sugar concentrations. Moreover, pretreatment solutions containing Na2CO3 improved the hydrolysis rates allowing SSB samples reach maximum yields faster than those without it, 48 versus 72 h. Results showed pretreatment methods combining NaOH and Na2CO3 were effective at promoting SSB biomass conversion, increasing sugar recovery after hydrolysis, and reducing the hydrolysis duration, all of which are desirable and cost beneficial.